Intellectual security for department managers - Abdukkah, Heba Naim Aldeen; Hussein, Thurayyah Ali (Al-Adab Journal, 2021)
Individuals differ in their level of intellectual stability and the ways in which they confront the crises facing them. Intellectual security is one of the terms that emerged as an inevitable consequence of the new intellectual influences resulting from the information openness and technological development, some of which were characterized by extremism and distance from moderation, and since the directors of departments in government institutions are one of the most important effective figures and leaders In the development and construction of society, it was imperative to give them clear attention in this field, Therefore, the researcher proceeded to conduct this kind of study, especially since we are living in this period of many pressures that pass on our country and its impact is reflected on members of society, and that these crises and pressures require studying the concept of Intellectual Security on a sample of department managers in government institutions because they are from Important elements that must be characterized by this concept. The current research aims to identify:Building a measure of intellectual securityMeasuring the intellectual security of department managers in governmental institutionsIdentify the differences in intellectual security of department managers according to the gender variable (male - female) To achieve the goals, the researcher relied on the theory of social disintegration in intellectual security. She also built a scale for intellectual security, and conducted statistical analyzes for the scale. The reliability coefficient for the Intellectual Security Scale was (0.92), and for the Cronbach Alpha method (0.96) After that, the measure was applied in its final form to the research sample, which numbered (400) managers and directors of a department in government institutions, and the data was processed statistically, and after analyzing the data, the following results were reached:1- Department managers possess a high level of intellectual security2- The level of intellectual security according to the gender variable is high for females compared to males